The Lund University Checklist for Incipient Exhaustion: a prospective validation of the onset of sustained stress and exhaustion warnings - Kai Österberg; Roger Persson; Njördur Viborg; Peter Jönsson; Artur Tenenbaum (BMC, 2016)
Abstract Background The need for instruments that can assist in detecting the prodromal stages of stress-related exhaustion has been acknowledged. The aim of the present study was to evaluate whether the Lund University Checklist for Incipient Exhaustion (LUCIE) could accurately and prospectively detect the onset of incipient exhaustion and to what extent work stressor exposure and private burdens were associated with increasing LUCIE scores. Methods Using surveys, 1355 employees were followed for 11 quarters. Participants with prospectively elevated LUCIE scores were targeted by three algorithms entailing 4 quarters: (1) abrupt onset to a sustained Stress Warning (n = 18), (2) gradual onset to a sustained Stress Warning (n = 42), and (3) sustained Exhaustion Warning (n = 36). The targeted participants' survey reports on changes in work situation and private life during the fulfillment of any algorithm criteria were analyzed, together with the interview data. Participants untargeted by the algorithms constituted a control group (n = 745). Results Eighty-seven percent of participants fulfilling any LUCIE algorithm criteria (LUCIE indication cases) rated a negative change in their work situation during the 4 quarters, compared to 48 % of controls. Ratings of negative changes in private life were also more common in the LUCIE indication groups than among controls (58 % vs. 29 %), but free-text commentaries revealed that almost half of the ratings in the LUCIE indication groups were due to work-to-family conflicts and health problems caused by excessive workload, assigned more properly to work-related negative changes. When excluding the themes related to work-stress-related private life compromises, negative private life changes in the LUCIE indication groups dropped from 58 to 32 %, while only a negligible drop from 29 to 26 % was observed among controls. In retrospective interviews, 79 % of the LUCIE indication participants confirmed exclusively/predominantly work stressors, while 6 % described a predominance of private life stressors. Conclusions Negative changes in the work situation were the most prominent change related to a sustained increase in LUCIE scores. The findings seem to confirm that LUCIE is a potentially useful tool for clinical screening of incipient work-related exhaustion.